Kritik Terhadap Pemikiran Samuel P. Huntington - M. Faturrohman Attirmidzi (FISIP UMY, 2015)
After Cold Wai, a political scientst of United Stabs, Samuel P Huntington, said thal West enemy afrer destruction of Uni Soviet communism is non economic problem or idoology but civilizalion. According to Huntington, lslam civilization will become lhe threat for Westem civilization so hat result he clash ot civilizations betlren lslam and West. Erpr6ssl, Huntington give he concrete example aboul existence of lslam threat to Wesl is appearance of exhemisl lslam which always break lhe West icons in Middle East and ofier states fiat alliance wift West. This adicle will discuss about cdlicisms of Huntington's opinion about the clash of civilizations betvJeen lslam and West.